DISAIN MODUL PRAKTIKUM SISTEM KENDALI DUA MOTOR INDUKSI DENGAN TEKNIK FUNCTION BLOCK MENGGUNAKAN PLC, MAD11 DAN VFD - Raden Hernadi; Pandi Sutardi; Siti Fatimatul Zuhro; Adelia Dwi Valentin (Jurnal Teknik dan Science, 2025)
The control and monitoring system for induction motor speed is widely used in industrial environments, specifically in the cable industry. The use of two working induction motors is for driving two extrusion machines that produce cables. Each machine operates according to a specific formula uploaded to the program. The main machine produces molten plastic in larger volumes, while the smaller machine applies coloring to the surface of the cable. However, the limited number of experts in this field often makes the industry experience difficulties when designing, modifying or when problems occur in the production machine control system program, so that foreign experts often have to be called in to handle it. To overcome this challenge, Educational Institutions need to prepare engineering students to be equipped with automation knowledge and practical experience through practical modules that enable them to design and implement HMI and PLC. This research aims to design a learning medium for industrial automation lab practice to enhance students' skills by mastering the concept of controlling two induction motors in the cable industry, where the motor speeds follow a formula similar to a linear equation uploaded to the Programmable Logic Controller (PLC) program.